2012
DOI: 10.1021/ja300901e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Dielectric Constant of the Surrounding Medium and the Substrate on the Surface Plasmon Resonance Spectrum and Sensitivity Factors of Highly Symmetric Systems: Silver Nanocubes

Abstract: Silver nanocubes (AgNCs), 60 nm, have four extinction surface plasmon resonance (SPR) peaks. The finite difference time domain (FDTD) simulation method is used to assign the absorption and scattering peaks and also to calculate the plasmon field intensity for AgNCs. Because AgNCs have a highly symmetric cubic shape, there is a uniform distribution of the plasmon field around them, and they are thus sensitive to asymmetric dielectric perturbations. When the dielectric medium around a nanoparticle is changed ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 43 publications
(95 reference statements)
7
141
1
Order By: Relevance
“…They have found applications in many different areas such as catalysis (Yacamán et al, 2001;Zhang et al, 2013), electronics (Li et al, 2005), optical sensing (Wang et al, 2012;Li et al, 2015) and biosensing (Walcarius et al, 2013). Numerous publications for synthesis of silver (Maria et al, 2013;Dong et al, 2009;Hu et al, 2004;Zhang et al, 2011;Mahmoud et al, 2012;Qin et al, 2010;Chekin & Ghasemi, 2014) and copper (Salavati-Niasari & Davar, 2009;Youngil et al, 2008;Zhu et al, 2005;Ramyadevi et al, 2012;Zain et al, 2014;Valodkar et al, 2011) colloids have been reported, and the most frequently used method is a chemical reduction of their ions, whereas various reducing and stabilizing agents were used. So far it has been reported the use of ascorbic acid as a reducing agent for metal NPs synthesis by using microwave irradiation (Qin et al, 2010;Chekin and Ghasemi, 2014).…”
Section: Metalmentioning
confidence: 99%
“…They have found applications in many different areas such as catalysis (Yacamán et al, 2001;Zhang et al, 2013), electronics (Li et al, 2005), optical sensing (Wang et al, 2012;Li et al, 2015) and biosensing (Walcarius et al, 2013). Numerous publications for synthesis of silver (Maria et al, 2013;Dong et al, 2009;Hu et al, 2004;Zhang et al, 2011;Mahmoud et al, 2012;Qin et al, 2010;Chekin & Ghasemi, 2014) and copper (Salavati-Niasari & Davar, 2009;Youngil et al, 2008;Zhu et al, 2005;Ramyadevi et al, 2012;Zain et al, 2014;Valodkar et al, 2011) colloids have been reported, and the most frequently used method is a chemical reduction of their ions, whereas various reducing and stabilizing agents were used. So far it has been reported the use of ascorbic acid as a reducing agent for metal NPs synthesis by using microwave irradiation (Qin et al, 2010;Chekin and Ghasemi, 2014).…”
Section: Metalmentioning
confidence: 99%
“…Saline may be a poor extract medium because chloride ions in saline might react with Ag + ions from the devices (Rigo et al, 2012), leading to precipitate of AgCl, although no precipitates were observed in this study. AgNPs exhibit characteristic light absorbance at around 400 nm, which is due to the surface plasmon resonance effect (Mahmoud et al, 2012). Others have demonstrated the usefulness of UV-VIS in differentiating silver ions and AgNPs (Zook et al, 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[ 42 ] AgNC 60 nm on glass from El-Sayed et al includes PVP coating [ 43 ] and AgNC 60 nm on silicon from Ianoul and co-workers. [ 42 ] The gold nanostars value is from Hafner et al [ 44 ] and the gold nanoframe value is from El-Sayed et al [ 45 ] …”
Section: Supporting Informationmentioning
confidence: 99%